1988
DOI: 10.1128/iai.56.7.1760-1765.1988
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of immunity to Eimeria vermiformis in mice by L3T4+ T cells

Abstract: Immunity to infection with Eimeria vermiformis was transferred in NIH mice by both the nylon wooladherent (B-cell-enriched) and nonadherent (T-cell-enriched) fractions of lymphocytes (spleen and mesenteric lymph node) taken from infected donors. Transfer was more variable with the adherent fraction, and when contaminating T cells were removed by treatment with anti-Thyl monoclonal antibody (MAb) and complement, this fraction lost all protective activity. The protective effect of T-cell-enriched populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…As anticipated from the results of previous work (Rose et al 1992(Rose et al , 1988, Figure 2 shows that in the control (shamvaccinated) mice of both strains, infections were greatly enhanced by CD4 cell depletion and less affected by depletion of CD8 cells. Also evident, in the undepleted mice, are the contrasting effects of vaccination on challenge infection, i.e.…”
Section: Effects Of Anti-cd4 or Anti-cd8 -Depleting Antibodiessupporting
confidence: 81%
See 1 more Smart Citation
“…As anticipated from the results of previous work (Rose et al 1992(Rose et al , 1988, Figure 2 shows that in the control (shamvaccinated) mice of both strains, infections were greatly enhanced by CD4 cell depletion and less affected by depletion of CD8 cells. Also evident, in the undepleted mice, are the contrasting effects of vaccination on challenge infection, i.e.…”
Section: Effects Of Anti-cd4 or Anti-cd8 -Depleting Antibodiessupporting
confidence: 81%
“…The interval between the doses was 6 days, the last dose being given 2 days before challenge with E. vermiformis. This regimen has been shown to result in signi®cant depletion of CD4 or CD8 cells during the replicative phase of the life-cycle of the parasite (Rose et al 1988, Rose et al 1992.…”
Section: Depletion Of Lymphocytes In Vivomentioning
confidence: 99%
“…38,40 In those studies, MLN cells were more effective than spleen cells. 40 Days p.i. Successful transfer and repopulation of recipients with cd cells was determined by¯ow cytometry.…”
Section: Adoptive Transfer Of Mln Cells From Naive and Infected Tcr-bmentioning
confidence: 93%
“…2), containing 2% FCS, with no cells. Recipient mice were challenged with E. vermiformis 24±48 hr after adoptive transfer, as described by Rose et al 38,40 Flow cytometry Cells were washed and resuspended at 5r10 6 /ml in staining buffer at 4u (PBS pH 7 . 2, 2% FCS, 0 .…”
Section: Adoptive Transfermentioning
confidence: 99%
“…During the years much attention has been concentrated on the role that different T cell subsets and cytokines play in generating protective responses against Eimeria infections (reviewed in Ovington et al 1995). In the rodent Eimeria model, adoptive transfer and in vivo depletion studies suggested a role for CD4 þ cells in the induction of immunity and the control of primary infections; whereas a role for CD8 þ cells was hypothesized to become functional after challenge infection (Rose et al 1988(Rose et al , 1992. IFN-g, a cytokine that has been demonstrated to play a key role in protozoan infections such as Leishmania (Scott 1991), Plasmodium (Schofield et al 1987), and Toxoplasma (Suzuki et al 1988), has also been implicated in the control of Eimeria infections.…”
Section: Introductionmentioning
confidence: 99%